Analisis Potensi dan Tantangan dalam Penggunaan AI di Bidang Pendidikan - Revalya Nadya; Ika Amalia; Ichsan Fauzi Rachman (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The development of Artificial Intelligence (AI) technology in the education sector has undergone major changes. These changes bring great opportunities to change the learning process to be more personal, effective, and inclusive. The purpose of this journal is to analyze the potential and challenges that need to be faced in the application of AI in education so that it can run optimally. The method used in this study is the literature review method of various recent studies that discuss the use of AI in education, The results of the study show that AI has great potential to improve the personalization of learning and educational efficiency. However, there are number of significant challenges, such as limited infrastructure, privacy and data security issues, resistance from educators and students, and the digital divide that still occurs in several regions. Therefore, a strategy is needed that includes a academic laziness that reduces learning motivation, constraints on AI contextual knowledge, Inability to process complex information, loss of literacy skills, amd the risk of addiction to AI technology. With a planned and sustainable strategy, AI has great potential to improve the quality of national education and also reduce the dangers that may arise from the modern technological era.